2023
DOI: 10.1038/s41598-023-38174-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in atmospheric circulation and evapotranspiration are reducing rainfall in the Brazilian Cerrado

Abstract: Here we analyze the trends of rainfall and the frequency of rainy days over the Brazilian Cerrado between 1960 and 2021 in four distinct periods according to the seasonal patterns over the region. We also evaluated trends in evapotranspiration, atmospheric pressure, winds, and atmospheric humidity over the Cerrado to elucidate the possible reasons for the detected trends. We recorded a significant reduction in rainfall and frequency of rainy days in the northern and central Cerrado regions for all periods exce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Conversely, in scenarios of future deforestation, precipitation reductions are even more pronounced, driven by a negative feedback mechanism. Hofmann et al 62 revealed a significant reduction in both rainfall and the frequency of rainy days in the northern and central regions of the Cerrado for all periods, except at the beginning of the dry season. The most pronounced negative trends were observed during the dry season and the early wet season, with reductions of up to 50% in total rainfall and the number of rainy days.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Conversely, in scenarios of future deforestation, precipitation reductions are even more pronounced, driven by a negative feedback mechanism. Hofmann et al 62 revealed a significant reduction in both rainfall and the frequency of rainy days in the northern and central regions of the Cerrado for all periods, except at the beginning of the dry season. The most pronounced negative trends were observed during the dry season and the early wet season, with reductions of up to 50% in total rainfall and the number of rainy days.…”
Section: Introductionmentioning
confidence: 94%
“…The most pronounced negative trends were observed during the dry season and the early wet season, with reductions of up to 50% in total rainfall and the number of rainy days. Hofmann et al 62 attributed to the intensification of the South Atlantic Subtropical Anticyclone, which has altered atmospheric circulation and increased regional subsidence. Additionally, reduced regional evapotranspiration during the dry season and early wet season likely contributed to the observed rainfall reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation